KEANEKARAGAMAN JENIS BURUNG DI TAMAN HUTAN RAYA SULTAN SYARIF HASYIM PROVINSI RIAU - Badriansyah, Rohmad; Hadinoto, Hadinoto; Ikhwan, Muhammad (Wahana Forestra: Jurnal Kehutanan, 2019)
Birds are an animal that has an important role in the process of forest succession, plays a role in spreading seeds, helping pollination, and balancing ecosystems. Deforestation of forest areas in Riau has a high rate, this can be seen from the change in the function of forests into agricultural and plantation land. The Sultan Syarif Hasyim Forest Park (TAHURA) is a conservation area that has quite alarming conditions, of the forest area of ​​6,172 hectares, there are only 2,000 hectares left forested, while the rest have acacia forest cover, shrubs, oil palm plantations, rubber plantations . The assessment of bird diversity needs to be carried out in the Sultan Syarif Hasyim Tahura given the high level of habitat destruction. Birds in TAHURA Sultan Syarif Hasyim have 71 species of birds from 34 families and 13 orders, there are 5 nocturnal birds. The diversity index (H) ranges from 3.19 - 3.92, the evenness index type (E) ranges from 0.88 - 0.92 and the species richness index (R) ranges from 2.14 - 4.28.